Experimental evaluation of the aerodynamic rotor/propeller interactions in hybrid compound helicopters - Lefevre, L.; Delva, J.; Nowinski, V. (My University, 2021)
This paper focuses on the experimental evaluation of the rotor/propeller interactions in hybrid compound configurations. Experiments were conducted in the ONERA L2 large size-low speed wind tunnel with a 1/7.7 Dauphin 365N model and a four-bladed small-scale propeller. The exhaustive characterization of the propeller’s performance was previously realized. Measurements were conducted using two six-component scales, accelerometers, and toppers to monitor the rotational speeds. Different flight conditions were set with variating wind speed, propeller rotational speed, and propeller position. Comparing the isolated characterizations of the rotor and the propeller with the complete assembly highlighted the influence of the interactions on the performances of the rotating elements. Variating the location of the propeller around the helicopter allowed the determination of the optimal position to maximize the performance.